"Demanding a Share of Public Regard": African American Education at New Philadelphia, Illinois. Issue 2 (9th September 2013) - Agbe‐Davies, Anna S.; Martin, Claire Fuller
Abstract: New Philadelphia, Illinois, is thought to be the first town in the US formally established by an African American. Among founder "Free Frank" McWorter's priorities was that members of his family attend school, years before state law supported education for children not classified as "white." It is well established that a later schoolhouse, built around 1874, was racially integrated. However, conflicting interpretations of available evidence, such as oral histories and written reminiscences, raise questions about the way in which the earliest schools served the African American and European American families of the town. The authors use archaeological and documentary evidence to search for the location of the schoolhouse and reveal how residents of this multiracial town challenged prevailing norms of common school education. The written and material traces are faint, but qualitative and quantitative analyses of the available materials demonstrate the school's significance for the residents of this community on the Midwestern frontier.